Varied nitrogen versus phosphorus scaling exponents among shrub organs across eastern China. (February 2021) - Zhao, Mengying; Luo, Yongkai; Chen, Yahan; Shen, Haihua; Zhao, Xia; Fang, Jingyun; Hu, Huifeng
Highlights: The N vs. P scaling exponents varied among shrub organs. Plant functional groups, environmental factors and habitats affected the N vs. P scaling exponents. The drivers of the N vs. P scaling exponents differed between metabolic and structural organs. Abstract: The nitrogen (N) vs. phosphorus (P) scaling exponent, which reflects the trade-off between N and P investment, is an important parameter for predicting plant growth and vegetation productivity. Previous studies mainly focused on a single metabolic organ, and the difference in scaling exponents among different organs was insufficiently discussed. We systematically sampled 1532 shrub individuals grown under two habitats from 13 forest sites across eastern China, and measured the nutrient concentrations of different organs to explore the characteristics of the N vs. P scaling exponents and the underlying influencing factors. The N vs. P scaling exponents varied among shrub organs. Plant functional groups (PFGs), climate zones, soil nutrient status and habitats significantly affected the N vs. P scaling exponents. The N vs. P scaling exponents of stems and coarse roots for deciduous, legume and typical shrubs were higher than those of evergreen, non-legumes and understory shrubs, respectively, and were lower in tropical region than in other regions. Stems and coarse roots showed a resistant response to nutrient limitation and a compliant response to high nutrient availability. The N vs. P scaling exponents of leaves and fine roots were not affected by PFGs and were mainly controlled by soil P and N availability, respectively. Our results suggest that these variations in the N vs. P scaling exponents and their influencing factors among different plant organs should be considered when these exponents are used in stoichiometric growth models. These results advance our understanding of plant nutrient allocation strategy in response to functional groups and environmental changes.